PENGARUH KINERJA KEUANGAN TERHADAP CORPORATE SOCIAL RESPONSIBILITY PADA PERUSAHAAN SEMEN YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2017 - 2021 - LISA AYUNI; NAZULA NUUR AZIZAH; AHMAD KAMALUDIN; DWI ERMAYANTI SUSILO (JURNAL AKUNTANSI DAN KEUANGAN, 2022)
This study aims to analyze the impact of corporate social responsibility on the company's financial results. For this reason, quantitative research methods are used in this study. The subject of this research is monetary results, where the results of the budget may or may not affect CSR. The display used in this study is all cement companies that publish financial statements for 2017-2021 on the IDX by choosing a location that meets the criteria of www.idx.co.id. The results of the research of cement companies show that the regression variable is 0.002, because the value of the variable is smaller than 0.0